VALUASI EKONOMI KAWASAN ARBORETUM DIPTEROCARPACEAE UNIVERSITAS LANCANG KUNING - Sadjati, Emy; Zargustin, Dedi; Ikhwan, Muhammad (Wahana Forestra: Jurnal Kehutanan, 2015)
Arboretum as one example of ecosystems that have the diversity of flora and fauna requires good management, so as to provide benefits to the surrounding environment. Biological diversity (biodiversity) that exist in the Arboretum area is quite high. This is because the Arboretum has many species which are usually brought in from outside, then planted and maintained as a collection of plants for various purposes of academic activities, in addition to local species that live naturally in the Arboretum. Limited funds arboretum management and level of understanding about the functions and benefits of some of the arboretum, arboretum resulted in the existence of a very minimalist. This issue will greatly affect the existence of the arboretum in the future.The purpose of this study are aware of the economic value of the existing flora and fauna in the Dipterocarpaceae arboretum and get the benefits of environmental services for the around arboretum. Economic valuation of the timber is done by using the market price approach. To obtain economic value of wood made a simple calculation that the total timber volume multiplied by price per unit of wood. While the economic value of air services is divided into two parts namely the absorption of carbon dioxide by the market price method and coolness by using surrogate price method. Value of economic in Unilak dipterocarp arboretum of Rp. 15,538,672,849.13 consisting of timber economic value of Rp. 385,843,912.00 and the coolness of the economic value of Rp. 15,137,500,000.00 and carbon uptake value of Rp. 15,078,937.13. The economic value of benefits in the form of services (intangible) greater (97.52%) than the value in the form of objects (tangible) (2.48%).